Elevated NLR May Be a Feature of Pediatric Brain Cancer Patients - Yalon, Michal; Toren, Amos; Jabarin, Dina; Fadida, Edna; Constantini, Shlomi; Mehrian-Shai, Ruty (Frontiers in Oncology, 2019)
Pediatric brain tumors are the most common solid tumor type and the leading cause of cancer-related death in children. The immune system plays an important role in cancer pathogenesis and in the response to immunotherapy treatments. T lymphocytes are key elements for the response of the immune system to cancer cells and have been associated with prognosis of different cancers. Neutrophils on the other hand, which secrete pro-angiogenic and anti-apoptotic factors, enhance the ability of tumor cells to grow and develop into metastases. We conducted a retrospective study of 120 pediatric brain cancer patients and 171 elective pediatric patients hospitalized in Dana Children’s Hospital and Sheba Medical Center. Data on age, sex, treatment, lymphocyte, neutrophil and monocyte count were collected from routinely performed preoperative blood tests. Neutrophil-to-lymphocyte ratio (NLR), and the lymphocyte-to-monocyte ratio (LMR) were calculated and significance was determined by paired T test. p<0.05 was considered as statistically significant. Neutrophils-to-lymphocyte ratio (NLR) was significantly higher in the pediatric brain cancer patients. The high NLR in pediatric brain cancer patients is the result of a combination of low lymphocytes and high neutrophils. Both of these factors can have a role in cancer development and propagation and also in response to therapy.